Socialization of Stunting Prevention Through Consumption of Fish Products for Students of SMA Negeri 2 Muara Sugihan, Banyuasin Regency, South Sumatera Province - Nasyiruddin, Riya Liuhartana; Utpalasari, Rih Laksmi; Sofian, Sofian; Jaya, Fitra Mulia; Yusanti, Indah Anggraini; Sulieman, Abdellatief A.; Nurhadiansyah, Muhammad Irvan; Nugroho, Yonathan Paskah Tri (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this community service is to provide education about stunting and the use of fish products to prevent stunting to the students at SMA Negeri 2 Muara Sugihan, Banyuasin Regency. The method used in community service activities was socialization of stunting prevention through consumption of fish products for high school students, using public lectures and demonstrations with predetermined themes. The community service activity is expected to have a positive impact in an increasing of students' understanding for stunting and its prevention by consuming various processed fish products. The results of implementing community service were evaluated regarding students' understanding of the material presented in the form of achievement indicators and benchmarks. Based on the results of implementing community service, participants were able to understand the definition, causes and ways to prevent stunting. Then the participants were also able to understand the nutritional content of fish and its benefits in preventing stunting. In addition, the participants have learned about various types of processed fish products. Overall, consumption of fish products is beneficial to prevent in developing countries occurrence of stunting through application of nutritional education in community service activities.